Repeatability, reproducibility, and accuracy of quantitative mri of the breast in the community radiology setting. Issue 3 (23rd March 2018) - Sorace, Anna G.; Wu, Chengyue; Barnes, Stephanie L.; Jarrett, Angela M.; Avery, Sarah; Patt, Debra; Goodgame, Boone; Luci, Jeffery J.; Kang, Hakmook; Abramson, Richard G.; Yankeelov, Thomas E.; Virostko, John
Abstract : Background: Quantitative diffusion‐weighted MRI (DW‐MRI) and dynamic contrast‐enhanced MRI (DCE‐MRI) have the potential to impact patient care by providing noninvasive biological information in breast cancer. Purpose/Hypothesis: To quantify the repeatability, reproducibility, and accuracy of apparent diffusion coefficient (ADC) and T1 ‐mapping of the breast in community radiology practices. Study Type: Prospective. Subjects/Phantom: Ice‐water DW‐MRI and T1 gel phantoms were used to assess accuracy. Normal subjects ( n = 3) and phantoms across three sites (one academic, two community) were used to assess reproducibility. Test–retest analysis at one site in normal subjects ( n = 12) was used to assess repeatability. Field Strength/Sequence: 3T Siemens Skyra MRI quantitative DW‐MRI and T1 ‐mapping. Assessment: Quantitative DW‐MRI and T1 ‐mapping parametric maps of phantoms and fibroglandular and adipose tissue of the breast. Statistical Tests: Average values of breast tissue were quantified and Bland–Altman analysis was performed to assess the repeatability of the MRI techniques, while the Friedman test assessed reproducibility. Results: ADC measurements were reproducible across sites, with an average difference of 1.6% in an ice‐water phantom and 7.0% in breast fibroglandular tissue. T1 measurements in gel phantoms had an average difference of 2.8% across three sites, whereas breast fibroglandular and adipose tissue had 8.4% and 7.5% average differences, respectively. In the repeatability study, we found no bias between first and second scanning sessions ( P = 0.1). The difference between repeated measurements was independent of the mean for each MRI metric ( P = 0.156, P = 0.862, P = 0.197 for ADC, T1 of fibroglandular tissue, and T1 of adipose tissue, respectively). Data Conclusion: Community radiology practices can perform repeatable, reproducible, and accurate quantitative T1 ‐mapping and DW‐MRI. This has the potential to dramatically expand the number of sites that can participate in multisite clinical trials and increase clinical translation of quantitative MRI techniques for cancer response assessment. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2018;48:695–707.